KAJIAN SUMBER CEMARAN MIKROBIOLOGIS PANGAN PADA BEBERAPA RUMAH MAKAN DI LINGKAR KAMPUS IPB DARMAGA, BOGOR - Siti Nurjanah (Institut Pertanian Bogor, 2006)
Food borne diseases by microganism was still happened as a lot of cases per annum. Sources of food microbiological contamination were raw materials, personal hygiene, sanitary of equipment and airborne and water sources. The goal of this research was to sources of food microbiological contamination in five restaurant around IPB campus which sould “pecel ayam”. Microbiological testing was conducted by total plate count, most probable number of coliform and biochemical identification of salmonella sp. And escherhicia colli. Personal hygiene and sanitaryof water and equipment testing have been done to detect sources of microbiological contamination. Food without heat teratment (cucumber) has a large amount of microganism (2.9-6.8 log CFU/g) and coliform (2.5-3.7 log MPN/g). smoked and fried chicken have total microoganism under 1.4 log CFU/g and total coliform under 0.3 log MPN/g. Sambal have total microoganism between 1.4-4.1 log CFU/g and total 0.3-4.1 log MPN/g. Neither Entorocbater aerogenes, nor Escherichia coli, the bacterium cold occasionally cause gastroenteritis, was identified from all of the smoked and fried chicken. E. coli has been isolated from cucumber of RM3, and the best possibility source of this bacterium was water source. Source of Entrobacter aerogenesis which identified from cucumber and sambal were personal handed, talenan and water source. Salmonella has not been identified from the entire sample.